Attribution of dispersal limitation can better explain the assembly patterns of plant microbiota - Li, Taiqiang; Gao, Jiangyun (Frontiers in Plant Science, 2023)
Disentangling community assembly processes is crucial for fully understanding the function of microbiota in agricultural ecosystems. However, numerous plant microbiome surveys have gradually revealed that stochastic processes dominate the assembly of the endophytic root microbiota in conflict with strong host filtering effects, which is an important issue. Resolving such conflicts or inconsistencies will not only help accurately predict the composition and structure of the root endophytic microbiota and its driving mechanisms, but also provide important guidance on the correlation between the relative importance of deterministic and stochastic processes in the assembly of the root endophytic microbiota, and crop productivity and nutritional quality. Here, we propose that the inappropriate division of dispersal limitation may be the main reason for such inconsistency, which can be resolved after the proportion of dispersal limitation is incorporated into the deterministic processes. The rationality of this adjustment under the framework of the formation of a holobiont between the microbiome and the plant host is herein explained, and a potential theoretical framework for dynamic assembly patterns of endophytic microbiota along the soil-plant continuum is proposed. Considering that the assembly of root endophytic microbiota is complicated, we suggest caution and level-by-level verification from deterministic processes to neutral components to stochastic processes when deciding on the attribution of dispersal limitation in the future to promote the expansion and application of microbiome engineering in sustainable agricultural development based on community assembly patterns.